PENGARUH PROFITABILITAS, LEVERAGE, KEPEMILIKAN SAHAM PUBLIK DAN UMUR PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN SUKARELA (Studi Empiris pada Perusahaan Industri Barang konsumsi yang terdaftar di BEI periode 2017 - 2018): PENGARUH PROFITABILITAS, LEVERAGE, KEPEMILIKAN SAHAM PUBLIK DAN UMUR PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN SUKARELA (Studi Empiris pada Perusahaan Industri Barang konsumsi yang terdaftar di BEI periode 2017 - 2018) - wirasandy wirasandy; Masiyah Kholmi; Riska Dwi Harventy (Universitas Gajayana Malang, 2019)
Abstract This study aims to detemine the effect of probability, leverage, public share ownership and company age on the extent of voluntary disclosure. The type of data used in study is a secondary data source in the form of a company’s annual report. Data sources were obtained from the official website of the Indonesia Stock Eschange, namely www.idx.co.id and the websites of each company. The data collection technique is done using the documentation method. Data analysis techniques used descriptive analysis, the classic assumption test, multiple linear regression analysis and hypothesis testing using statistical tools SPSS V>24. Based on the result of the study, the authors can conclude that profitability, public share ownership dan age of the company affect the area of voluntary disclosure while leverage does not affect the area of voluntary disclosure. Keywords : Profitability, Leverage, Public Share Ownership, Company Age, Extensive voluntary disclosure.